An economic assessment of adoption of hybrid rice: Micro-level evidence from southern China - Yan, Zedong; Chen, Fengbo; Mishra, Ashok K.; Sha, Wenbiao (Frontiers in Sustainable Food Systems, 2022)
The hybrid rice technology could be considered a boon for food security for many in South and Southeast Asia to increase rice productivity. In China, the birthplace of hybrid rice(HR), the diffusion of hybrid rice started in 1976. About 28% of China’s rice-growing area is planted with hybrid rice. However, the proportion of HR area in China is declining in recent years, and farmers in surrounding countries are reluctant to adopt it because of high seed costs, farm management practices, and quality issues. Most previous research on evaluation of hybrid rice variety on yield didn’t control input level.Using plot- and household-level data, we analyze the impacts of HR adoption on rice yields and income in four southern provinces of China. The study accounts for observed and unobserved heterogeneity using endogenous switching regression. Findings show a significant effect of HR adoption on rice yields. Rice yield increases by 4.86% for HR adopters. Rice yields would increase by 4.72% if the HR variety was adopted on conventional rice plots. Additionally, findings show that HR adopters increase net rice incomes by 43.61% if the conventional rice is adopted on HR rice plots. Similarly, net rice income decreases by 10.95% if the HR variety is adopted on conventional rice plots. Thus, the adoption of HR increases rice productivity, but Chinese farming households that adopted conventional rice would not benefit from adopting hybrid rice.